TEKANAN EKONOMI, MANAJEMEN KEUANGAN, DAN KESEJAHTERAAN PADA KELUARGA MUDA - Raharjo, Iman Teguh; Puspitawati, Herien; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
Financial problem is a common problem experienced by young families. Economic limitedness is often the source of conflict between husband and wife. This makes the families become depressed. Good financial management is expected to neutralize economic pressure faced by young families so that this won’t disturb the process of interaction that can affect family welfare. This research aimed to analyze objective and subjective economic pressure, financial management, objective and subjective welfare of young families. This research used cross sectional design involving 120 young families with maximum age of husband was 30 years old and also had at least one child under 6 years old. The sampling was done by using stratified nonpropotional random sampling with the age of wives ranging from <20 years old and 20-30 years old at two areas in Cipayung Sub District, Depok City, West Java. Based on regression analysis, it could be found out that financial management affected the subjective family welfare positively. On the other hand, subjective economic pressure influenced the subjective welfare negatively.